Access to finance and exporting behavior in transition countries - Alex Bernard; Augusto Stabilito; Julian Donghoon Yoo (Kiel Institute for the World Economy (IfW), 2010)
We analyze the link between firms' access to finance and their decisions to enter and exit the export market. We employ the Business Environment and Enterprise Performance Survey (BEEPS) conducted in 2005 and 2008-2009 to 28 countries in Eastern Europe and Central Asia. We find that more productive, foreign owned and older firms are more likely to start exporting, while larger and more productive firms are less likely to exit the export market. With respect to ex-ante firm characteristics, our results confirm that larger and more productive, as well as foreign-owned, firms self-select into exporting. By contrast, there is no relationship between the decision of firms to enter or exit export markets and their access to finance. This may suggest that internal finance plays a greater role in Eastern European and CIS countries than in developed countries.
Keywords: F14; G32; L25; D92; 330; Exports; Firm heterogeneity; Access to finance; Exportindustrie; Markteintritt; Unternehmen; Finanzierung; Multinationales Unternehmen; Schätzung; Osteuropa; Zentralasien